2014
DOI: 10.1002/adma.201400918
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Low‐Power Pressure Sensor Matrix Based on Coplanar‐Gate Graphene Transistors

Abstract: A novel device architecture for preparing a transparent and low-voltage graphene pressure-sensor matrix on plastic and rubber substrates is demonstrated. The coplanar gate configuration of the graphene transistor enables a simplified procedure. The resulting devices exhibit excellent device performance, including a high transparency of ca. 80% in the visible range, a low operating voltage less than 2 V, a high pressure sensitivity of 0.12 kPa(-1) , and excellent mechanical durability over 2500 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 36 publications
1
136
1
3
Order By: Relevance
“…In fact, graphene based resistive-type pressure sensors have already been developed121314. A single-layer graphene suspended on a cavity12 was demonstrated to have a pressure sensing range of up to 100 kPa but with a rather small sensitivity (2.66 × 10 −5  kPa −1 ).…”
mentioning
confidence: 99%
“…In fact, graphene based resistive-type pressure sensors have already been developed121314. A single-layer graphene suspended on a cavity12 was demonstrated to have a pressure sensing range of up to 100 kPa but with a rather small sensitivity (2.66 × 10 −5  kPa −1 ).…”
mentioning
confidence: 99%
“…Furthermore, faster response time, high frequency operation (10 kHz) and solution process compatibility makes it a suitable dielectric material for flexible electronics applications. [42] Sun et al [43] reported a development of coplanar gate graphene field effect transistor matrix comprising ion gel as a gate dielectric for pressure sensing applications.…”
Section: Dielectricmentioning
confidence: 99%
“…The device had a high sensitivity of 0.12 kPa-1, low operation voltage and good mechanical stability. [43] These features are very attractive for e-skin in robotics, where fast, reliable and repeatable response is much desired. [2] Other graphene-based solutions, which can also be used in robotic systems, are flexible and transparent strain sensors, [83] flexible supercapacitors [84] and gas sensors on bendable and soft substrates.…”
Section: Carbon Based Materialsmentioning
confidence: 99%
“…In particular, the selection of suitable active materials plays an important role in dominating the performance of sensors. To date, various materials, including carbon nanotubes (CNTs) [11,[26][27][28][29][30], graphene [31][32][33][34][35][36][37][38][39][40], carbon black [41][42][43][44][45], conductive polymers [16,[46][47][48], metal nanoparticles (NPs) and nanowires [21,[49][50][51][52][53][54][55], semiconductors [56,57], have been used as the active components for the fabrication of flexible sensors. Among these materials, metal NPs can be used to fabricate flexible sensors with high sensitivity, but the sensing range and stretchability of these sensors are limited [58].…”
Section: Introductionmentioning
confidence: 99%